Reference values for performance test outcomes relevant to English female soccer players. Issue 5 (1st December 2022) - Datson, Naomi; Weston, Matthew; Drust, Barry; Atkinson, Greg; Lolli, Lorenzo; Gregson, Warren
ABSTRACT: The purpose of this study was to present reference standards for physical performance test outcomes relevant to elite female soccer players. We analysed mixed-longitudinal data (n = 1715 observations) from a sample of 479 elite youth and senior players as part of the English Football Association's national development programme (age range: 12.7 to 36.0 years). Semi-parametric generalized additive models for location, scale and shape (GAMLSS) estimated age-related reference centiles for 5-m sprinting, 30-m sprinting, countermovement jump (CMJ) height, and Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1) performance. The estimated reference centiles indicated that the median of the distribution of physical performance test scores varied non-linearly with advancing chronological age, improving until around 25 years for each performance variable. These are the first reference ranges for performance test outcomes in elite English female soccer players. These data can assist practitioners when interpreting physical test performance outcomes to track an individual's progress over time and support decision-making regarding player recruitment and development.